2012
DOI: 10.1007/s00192-012-1701-7
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual dysfunction: what Arab gynecologists think and know

Abstract: Our results reveal an apparent global lack of adequate education in female sexuality and expose the breadth of the problem among Arab Gyns. Therefore, there is a need to improve training at the undergraduate and postgraduate levels to enable Gyns in Arab countries to provide better sexual healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…However, because of cultural taboos, gynecologists in this society are rarely adequately trained to have the understanding, support, or compassion that is required to effectively treat female sexual dysfunction. 25 …”
Section: Discussionmentioning
confidence: 99%
“…However, because of cultural taboos, gynecologists in this society are rarely adequately trained to have the understanding, support, or compassion that is required to effectively treat female sexual dysfunction. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Prevalence estimates have shown that up to 64% of sexually active women attending an urogynecology clinic suffer from sexual dysfunction . Despite this, worldwide many health‐care professionals who treat women with PFD feel inadequately trained to approach the subject of sexual function: they do not know what/how to ask or are unsure about therapeutic options . Without health‐care professionals understanding patients' concerns, distressing sexual problems could go unnoticed as many women hesitate to present these symptoms to their doctors themselves .…”
Section: Introductionmentioning
confidence: 99%
“…In Tunisia as in other Arab Muslim countries, sexuality remains a taboo and a very sensitive subject, so patients do not generally consult directly a sex therapist but gynaecologists, as seen in our case series (Auwad and Hagi, 2012; Muammar et al ., 2015).…”
Section: Discussionmentioning
confidence: 81%